PIM research informs agricultural policies aimed at ensuring the long-term success of the 2018 Rice Tariffication Act in the Philippines - CGIAR Research Program on Policies, Institutions, and Markets (2019)
With PIM support, IFPRI collaborated with the National Economic and Development Authority (NEDA) to inform policies for food security and adaptation to climate change in the Philippines. A first outcome was the adoption of the Rice Tariffication Act in 2018. In 2019, the government followed IFPRI and NEDA recommendations on how to compensate rice farmers negatively affected by the tariffication policy by launching the Rice Farmer Financial Assistance and a plan to increased rice productivity and crop diversification.